(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. This article analyses professional self-improvement as one of the basic factors of personal growth of a future teacher. The different scientists’ approaches to defining the essence of professional self-improvement as a personally valuable and professionally important quality of a personality was considered presenting the main characteristics of this phenomenon. It was established that psychological basis of professional self-improvement is professional self-awareness, which contributes to the development of a future teacher as a subject of professional self-improvement. The main psychological determinants of the process of professional self-improvement of a personality and its characteristics were found and presented